Learning Arabic in the Digital Era (from Positive and Negative Aspects) | تعليم اللغة العربية في العصر الرقمي (من الجوانب الإيجابية والسلبية) - Syafa'ah, Siti Lailatus; Basyar, Syarifuddin; Hijriyah, Umi; Erlina; Kesuma, Guntur Cahya (NAJAH BESTARI, 2024)
The rapid development of technology has positive and negative impact on the world of education, for that this research aims to find the positive and negative impact that occurs as a result of progress of technology in the world of education. This type of research is a qualitative descriptive research, the aim of this research is to find the positive and negative impacts of the advancement of the digital era in the world of education which sometimes requires students to be proficient in using the internet.. In reality, there are still students who are not yet proficient in using the internet or do not have a device. The digital era in learning must also be supported by sufficient economy among students because using technology requires costs to use it. this is what happened in class V students at MI Al Khairiyah Krawangsari Natar. Technological advances in learning cannot be fully enjoyed by all students, due to the different economic and educational backgrounds of students' parents. The data in this research was obtained by interviews, observation and documentation. From the results of the research, it was found that the positive aspect of the digital era felt by teachers and students in MI Al Khairiyah Krawangsari Natar is that learning Arabic is more fun and of course this makes student learning outcomes increase, while the negative impact of the digital era is that students who don't have devices have to studying with friends, students who are not yet proficient in using the internet tend to be late in attending lessons and then feel lazy and bored in the learning process.